Marketing de serviços – análise da percepção da qualidade de serviços através da ferramenta SERVQUAL em uma instituição de ensino superior de Santa Catarina - Brígida Dettmer; Ceci Socorro; Heitor Takashi Katon (Revista de Ciências da Administração : RCA, 2002)
In the first part of this article it has been condensed the services marketing concepts since its beginning and the concepts about services quality. In the second chapter we tried to identify the main meaning of services quality and the costumer perception about it showing the difference between services quality and costumer satisfaction. After this it was done an analysis of the costumer hopes and how they feel quality. In the end of this article it has been studied the five quality dimensions computing the results of a SERVQUAL questionnaire that was applied in a college from Santa Catarina.